New and noteworthy records to the Angolan orchid flora revealed by the little-known watercolours of Helen Faulkner (1888–1979) - Bytebier, Benny (Phytotaxa, 2025)
Helen Faulkner lived in Angola between 1937 and 1942, where she collected and made watercolour sketches of the plants she encountered on her forays. Most of her herbarium specimens are preserved at the National Herbarium in Pretoria (PRE) and the Royal Botanic Gardens, Kew (K). Her botanical artwork, not only of plants from Angola but also of plants from Mozambique and Tanzania, is preserved in 18 notebooks deposited at the Archives of the Royal Botanic Gardens Kew. Many, but not all, of her watercolours are cross-referenced to herbarium specimens. This paper provides an identification for all 49 Angolan orchid sketches representing at least 46 different species. Only about half have a corresponding herbarium specimen of which the identification was also checked. Furthermore, comments are provided on some of the remarkable plants she saw, such as Eulophia obstipa, Platycoryne trilobata, and Habenaria decaptera. Four of the illustrated species represent new country records for Angola, namely Eulophia susbsaprophytica, Habenaria calvilabris, Habenaria gonatosiphon, and Orthochilus thomsonii.